Life skills in tarung derajat - Ulandari, Ulandari; Oktadinata, Alek; Putra, Anggrawan Janur; Adrizal, Mohd; Munar, Hendri (Jurnal Patriot, 2024)
Problem: Based on observations made by researchers at the Siginjai Museum, Jambi City, athletes are very skilled in combat sports, but are still lacking in terms of affectivity, where athletes are more selfish, get angry easily, have less respect for time, act as they please and do not follow the rules given by them. coach. Purpose: The purpose of this research is to find out how the implementation of the Tarung Derajat sports training program at the Siginjai Museum Satlat, Jambi City, affects athletes' life skills. Apart from that, we also want to know whether the life skills component is more dominant in the programmed training process. Method: This research was conducted at the Tarung Derajat Satlat, Siginjai Museum, Jambi City in February 2024. With a population of 60 people, the sample was active members aged 11-21 years with a minimum average of 2. This research data was obtained through a questionnaire, Likert scale and LSSS (Life Skill Scale Of Sport), Cornin and Allen 2017. This research is a quantitative descriptive research. The data collection technique used is descriptive statistics using the Triangulation Technique. In this research, the data collected includes information regarding 8 components of life skills for combat athletes based on the aspects discussed in the questionnaire. Results: From the results of the analysis of 8 life skills components, the results for teamwork were 82%, goal setting was 85.63%, time management was 60%, emotional skills were 58.79%, interpersonal communication was 77%, social skills were 77% . 80%, leadership at 79% and problem solving at 76%. Conclusion: The research results explain that the most dominant aspect is goal setting at 85.63%, while the lowest aspect is the emotional skill aspect at 58.79%.